2015
DOI: 10.2343/geochemj.2.0382
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a laccolith by magma pulses: Evidence from modal and chemical composition of the 500 m long borehole section through the Permo-Carboniferous Landsberg laccolith (Halle Volcanic Complex)

Abstract: However, chemical variations within the magma body could also be an evidence for fractional crystallization and/or magmatic segregation. Additional information that may help to indicate that internal heterogeneity in the magma body was due to separate magma pulses can be provided by application of quantitative textural analysis including modal abundance of minerals (Mock et al., 2003). In the current paper we use combined chemical and mineralogical analyses of selected samples from the 500 m long completely co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Zircon in Halle was often associated with other accessory minerals such as apatite, rutile, and Fe-oxide-forming veins that intruded later than the majority of the laccolith body. This would be in accordance with previous interpretations of multiple magmatic injections forming laccolith bodies [15,21,30], and would additionally suggest the presence of strongly differentiated melts during laccolith formation. As such, at least two populations occurred in Halle rhyolite-one in biotite, and one related to this later melt infiltration.…”
Section: New Insights Into Zircon Behavior In Silicic Magmas Based Onsupporting
confidence: 92%
See 4 more Smart Citations
“…Zircon in Halle was often associated with other accessory minerals such as apatite, rutile, and Fe-oxide-forming veins that intruded later than the majority of the laccolith body. This would be in accordance with previous interpretations of multiple magmatic injections forming laccolith bodies [15,21,30], and would additionally suggest the presence of strongly differentiated melts during laccolith formation. As such, at least two populations occurred in Halle rhyolite-one in biotite, and one related to this later melt infiltration.…”
Section: New Insights Into Zircon Behavior In Silicic Magmas Based Onsupporting
confidence: 92%
“…The Halle Complex comprises several fine-grained and coarse-grained laccoliths [19,20] emplaced from 291.7 ± 1.8 to 301 ± 3 Ma [19]. The individual laccoliths were formed by several successive magma pulses with evidence of the prolonged laccolith formation being consistent with structural, petrological, and geochemical data [15,21,22]. The sample analyzed in this study came from coarse-grained Landsberg laccolith that was shown to contain chemically and isotopically diverse zircon of Permian age, suggesting the presence of both antecrystic and autocrystic grains [23].…”
Section: Geological Settingsupporting
confidence: 56%
See 3 more Smart Citations